Is “Partners” (Cooperative Teaching and Learning) Method an effective Innovative teaching method for Arab Nursing Students? - Lakshmi, Renganathan; Salem, Al Touby (2014)
The global goal of the nurse educators is to develop initiatives and innovations which will prepare the nursing graduates for quality nursing practice. Faculty must help future nurse professionals to become self-directed learners and knowledgeable participants in Evidence Based Practice.